Genomic analysis of bluetongue virus episystems in Australia and Indonesia. (December 2017) - Firth, Cadhla; Blasdell, Kim; Amos-Ritchie, Rachel; Sendow, Indrawati; Agnihotri, Kalpana; Boyle, David; Daniels, Peter; Kirkland, Peter; Walker, Peter
Abstract The distribution of bluetongue viruses (BTV) in Australia is represented by two distinct and interconnected epidemiological systems (episystems)—one distributed primarily in the north and one in the east. The northern episystem is characterised by substantially greater antigenic diversity than the eastern episystem; yet the forces that act to limit the diversity present in the east remain unclear. Previous work has indicated that the northern episystem is linked to that of island South East Asia and Melanesia, and that BTV present in Indonesia, Papua New Guinea and East Timor, may act as source populations for new serotypes and genotypes of BTV to enter Australia's north. In this study, the genomes of 49 bluetongue viruses from the eastern episystem and 13 from Indonesia were sequenced and analysed along with 27 previously published genome sequences from the northern Australian episystem. The results of this analysis confirm that the Australian BTV population has its origins in the South East Asian/Melanesian episystem, and that incursions into northern Australia occur with some regularity. In addition, the presence of limited genetic diversity in the eastern episystem relative to that found in the north supports the presence of substantial, but not complete, barriers to gene flow between the northern and eastern Australian episystems. Genetic bottlenecks between each successive episystem are evident, and appear to be responsible for the reduction in BTV genetic diversity observed in the north to south–east direction.